Update on the Pharmacological Actions of Enoxaparin in Nonsurgical Patients - Egidio Imbalzano; Luana Orlando; Giuseppe Dattilo; Marianna Gigliotti De Fazio; Giuseppe Camporese; Vincenzo Russo; Alessandro Perrella; Francesca Futura Bernardi; Pierpaolo Di Micco (Medicina, 2024)
Low-molecular-weight heparins are a class of drugs derived from the enzymatic depolymerization of unfractionated heparin that includes enoxaparin. Several studies have been performed on enoxaparin in recent years, in particular for the prevention and treatment of venous thromboembolism and for the treatment of acute coronary syndrome. Furthermore, the use of enoxaparin has been extended to other clinical situations that require antithrombotic pharmacological prevention, such as hemodialysis and recurrent abortion. In this review, we report the main clinical experiences of using enoxaparin in the prevention of VTE in nonsurgical patients.